Academic performance at Adventist University of Chile during COVID-19: a comparative analysis 2019-2020 - Franco, Eduardo (2021)
The COVID-19 pandemic has forced public and private universities to adopt emergency instructional facilities. The impossibility of presence has forced distance learning and the adaptation of evaluation methods. It could be hypothesized that these changes could lead to a decrease in the academic performance of students. This work analyzes through a descriptive study the academic performance in the first semesters of 2019 and 2020 among the first-year students of the Adventist University of Chile with a sample of 641 students in specialty courses. Contrary to what was predicted by the researchers, the average academic performance improved in 2020 compared to 2019, this may be due to the innovative methodological strategies and flexibility policies adopted by the university.